1993
DOI: 10.1039/ft9938903419
|View full text |Cite
|
Sign up to set email alerts
|

Influence of electrostatic interactions on β-casein layers adsorbed on polystyrene latices

Abstract: Electrophoretic mobility, dynamic light scattering and solution-depletion measurements have been combined to study t h e influence of electrostatic interactions on the thickness and structure of adsorbed layers of p-casein at the solid/liquid interface (polystyrene latex particles). Charge effects are investigated by removing phosphate groups from the protein, by varying the ionic strength and by including divalent calcium ions which are known to bind to the protein in solution. The observations on hydrodynami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
3

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 20 publications
4
33
3
Order By: Relevance
“…The rates of decrease in thickness observed here ( Fig. 8) with added Ca 2ϩ in the 0 to 3 mmol dm Ϫ3 range are, however, somewhat lower that the sharp changes seen previously in the hydrodynamic layer thickness for ␤-casein coatings (21), although the final layer thicknesses are slightly lower at 4 nm as opposed to just under 6 nm for the hydrodynamic thickness for this protein. There are two possible contributory effects operating here.…”
Section: Effect Of Ca 2ϩ Additioncontrasting
confidence: 66%
“…The rates of decrease in thickness observed here ( Fig. 8) with added Ca 2ϩ in the 0 to 3 mmol dm Ϫ3 range are, however, somewhat lower that the sharp changes seen previously in the hydrodynamic layer thickness for ␤-casein coatings (21), although the final layer thicknesses are slightly lower at 4 nm as opposed to just under 6 nm for the hydrodynamic thickness for this protein. There are two possible contributory effects operating here.…”
Section: Effect Of Ca 2ϩ Additioncontrasting
confidence: 66%
“…Calcium binding to proteins reduces electrostatic repulsion between the molecules (24,25). Also, the reduction in the negative values of the -potential and the hydrodynamic diameter of protein-coated polystyrene lattices (26) agree with the fact that both the electrokinetic potential and steric repulsion are reduced when calcium binds to the interfacial proteins and this permits closer approach of the particles. This reduction in the interparticle distance between the emulsion droplets means that further associations like Van der Waals attraction, hydrogen bonding, inter-and intramolecular calcium cross-linking and hydrophobic interactions can more easily occur.…”
Section: Discussionsupporting
confidence: 51%
“…Earlier -casein QCM-D studies reported areal masses in agreement with our results [ 39 , 40 ]. Experimental works based on the batch depletion method [ 41 , 42 ] or ellipsometry [ 43 , 44 ] reported values of 2–3 mg/m 2 for a full-coverage monolayer of -casein. These results also support our interpretation that the value of 6.1 mg/m 2 obtained by QCM corresponds to multilayer formation.…”
Section: Resultsmentioning
confidence: 99%